2004
DOI: 10.1038/sj.ejhg.5201217
|View full text |Cite
|
Sign up to set email alerts
|

Survival motor neuron SMN1 and SMN2 gene promoters: identical sequences and differential expression in neurons and non-neuronal cells

Abstract: Spinal muscular atrophy (SMA) is a recessive disorder involving the loss of motor neurons from the spinal cord. Homozygous absence of the survival of motor neuron 1 gene (SMN1) is the main cause of SMA, but disease severity depends primarily on the number of SMN2 gene copies. SMN protein levels are high in normal spinal cord and much lower in the spinal cord of SMA patients, suggesting neuron-specific regulation for this ubiquitously expressed gene. We isolated genomic DNA from individuals with SMN1 or SMN2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…TSS1b was mapped in Echaniz-Laguna et al [30], and TSS3 was identified in Monani et al, [31]. Nucleotide differences between the SMN1 and SMN2 promoters are indicated based on Monani et al, [31]; [29, 32]), where nucleotide positions were calculated from TSS1a. Translation initiation site is marked as Start.…”
Section: Figmentioning
confidence: 99%
“…TSS1b was mapped in Echaniz-Laguna et al [30], and TSS3 was identified in Monani et al, [31]. Nucleotide differences between the SMN1 and SMN2 promoters are indicated based on Monani et al, [31]; [29, 32]), where nucleotide positions were calculated from TSS1a. Translation initiation site is marked as Start.…”
Section: Figmentioning
confidence: 99%
“…Although SMN expression is ubiquitous, its expression is highest in the central nervous system (Fig. 2D) (25), particularly in spinal motor neurons where the disease is manifested (5,6,26). To assess the activity of RN-0005 in disease-relevant cells, we examined SMN expression in two neuronal cell types.…”
Section: Prc2mentioning
confidence: 99%
“…Interestingly, the highest levels of SMN are detected in the ventral horn of the spinal cord and motor neurons [41,71], which are primarily affected in SMA. Accordingly, the strongest decline of SMN levels in SMA is also observed in these tissues [74]. Changes in gene expression patterns during development have previously been linked to epigenetic regulation [75].…”
Section: Hdac Inhibitors In Sma Treatmentmentioning
confidence: 81%